Triple-hit explanation for the worse prognosis of pediatric acute lymphoblastic leukemia among Mexican and Hispanic children - Rivera-Luna, Roberto; Perez-Vera, Patricia; Galvan-Diaz, Cesar; Velasco-Hidalgo, Liliana; Olaya-Vargas, Alberto; Cardenas-Cardos, Rocio; Aguilar-Ortiz, Marco; Ponce-Cruz, Jesus (Frontiers in Oncology, 2022)
Acute lymphoblastic leukemia (ALL) is the most common malignancy among Mexican and Hispanic children and the first cause of death by disease in Mexico. We propose a “triple-hit” explanation for the survival gap affecting this population. The first hit can be attributed to epidemiology and social, cultural, and economic burdens. The second hit refers to cancer biology, with a high incidence of unfavorable genetic characteristics associated with an unfavorable response to treatment and, subsequently, poor survival. Finally, the third hit relates to sub-optimal treatment and support. Society and culture, leukemia biology, and treatment approach limitations are key factors that should not be seen apart and must be considered comprehensively in any strategy to improve the prognosis of Mexican and Hispanic children with ALL.